STRATEGI PENINGKATAN MORAL DAN SIKAP PADA PEMBELAJARAN PKN DI SEKOLAH DASAR - Muhammad Radit; Razi Hasbullah; Hima Sisri Wahyuni; Elfia Sukma; Inggria Kharisma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
National education aims to develop students' potential to become faithful and noble individuals, yet contemporary challenges such as moral degradation and the negative influence of digital technology pose serious obstacles at the elementary school level. This study aims to examine various implementative strategies in Civic Education (PKn) to enhance students' morals and attitudes. The method used is a library research with a Systematic Literature Review approach, analyzing scientific articles published within the last five years. The results indicate that innovative strategies such as the Value Clarification Technique (VCT) model, Problem Based Learning (PBL), the integration of character education into the curriculum, and the development of civic disposition are effective in improving student behavior. Furthermore, teacher modeling and synergy between the school environment and families are decisive factors for the consistent internalization of Pancasila values. Proper strategy implementation is proven to increase empathy, responsibility, and minimize conflicts among students.